2014
DOI: 10.1111/imm.12212
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab‐induced interleukin‐15 reduction associated with clinical improvement in rheumatoid arthritis

Abstract: SummaryRituximab therapy alters all aspects of B-cell participation in the disturbed immune response of rheumatoid arthritis patients. To determine the impact of B-cell depletion on other immune compartments, we analysed levels of soluble and surface interleukin-15 (IL-15) along with the frequency of IL-15-related subsets after rituximab treatment. We then studied the correlation of observed changes with clinical activity. Heparinized blood samples from 33 rheumatoid arthritis patients were collected on days 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Several investigators have reported that Treg cells from AAV patients had a decreased suppressive function , even in remission and in the absence of any immunosuppressant . With regard to the effects of B cell depletion therapy on Treg cells, contradictory data have been reported in studies performed in various settings such as cryoglobulinemic vasculitis , RA , systemic lupus erythematosus (SLE) , and autoimmune thrombocytopenia . Importantly, most of those data were from uncontrolled longitudinal studies using simple staining strategies for Treg cell identification.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported that Treg cells from AAV patients had a decreased suppressive function , even in remission and in the absence of any immunosuppressant . With regard to the effects of B cell depletion therapy on Treg cells, contradictory data have been reported in studies performed in various settings such as cryoglobulinemic vasculitis , RA , systemic lupus erythematosus (SLE) , and autoimmune thrombocytopenia . Importantly, most of those data were from uncontrolled longitudinal studies using simple staining strategies for Treg cell identification.…”
Section: Discussionmentioning
confidence: 99%
“…+ T and NK cell responses in other diseases such as rheumatoid arthritis (44)(45)(46) and multiple sclerosis (47), suggesting that the enlarged infarct size seen in GFAP-IL-15 tg mice may result from the enhanced CD8 + T and NK responses. This notion is supported by the observation of an astrocytic IL-15-induced increase of activated CD8 + T and NK cells, which suggests the involvement of direct cytotoxicity by CD8 + T and NK cells in postischemic lesion enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…IL-15 is an inflammatory cytokine with a function on a wide range of immune cells ( 27 , 28 ). Much evidence demonstrated that IL-15 can boost immune cells to exacerbate disease progression such as rheumatoid arthritis and stroke ( 13 15 , 29 ). However, there are still documents, which demonstrated that IL-15 is beneficial to experimental autoimmune encephalomyelitis ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%